A Research on Passenger Carrying Capacity of an Innovative Electric Traction Power Supply System based on ROCS of 750 V DC MRT - Thai, Nguyen; Doan Van, Dong (Engineering, Technology & Applied Science Research, 2024)
This article presents the results of a study on the feasibility of a Rigid Overhead Conductor-rail System (ROCS) for a Mass Rapid Transit (MRT) system using 750 V DC power based on a carrying capacity transport-supply voltage level relationship. In particular, peak load conditions often cause serious problems of voltage drops occurring along the contact line, affecting the reliability, flexibility, system safety, and efficiency performance of the MRT system. The potential at the pantograph of a train on the segment of power supply depends significantly on the structure of the traction power supply network, contact network type, and voltage level. Recently, there have been studies on the dynamics of ROCSs under the impact of train motion, thereby applying the design to several railway systems in the world in specific conditions such as tunnels, stations, or viaducts. To consolidate the advantages of this trend, this paper studies the operating voltage of an ROCS in a full-line MRT system with a voltage level of 750 V DC belonging to the third rail. Matlab R2017b/Railway Systems is a reliable software for simulating and analyzing the necessary data. The results exhibit the feasibility of the designed ROCS. The system has a passenger carrying capacity of up to 90,000 passengers per hour per direction (p/h/d) under both normal and fault conditions. In this case, this capacity is achieved with a single-end feed at a distance of 2 km from a Traction Power Station (TPS), with the minimum feeder voltage at the pantograph point being 532.7200 V. The lowest operational feeder voltage of the system is 523.6667 V, supplied from a double-end feed at a distance of up to 5 km from the TPS.